Wood-derived ultra-high temperature carbides and their composites: A review. Issue 5 (1st April 2020) - Yu, Min; Zhang, Guo-jun; Saunders, Theo
Abstract: Wood gains much attention owing to its unique characters such as cellular pore structures, low density etc. Wood-derived carbides have great potential applications as the high-temperature filters for gas or liquid, catalyst carrier, fluid/gas reservoir devices, biocatalyst supports, etc. In this paper, we review recent progress in comprehensively understanding the processing techniques, properties and applications of wood-derived carbides. The key techniques for producing wood-derived carbides involves the infiltration techniques which are categorized into six parts (slurry infiltration, polymer precursor infiltration, melting infiltration, molten salt infiltration, sol-gel infiltration, and chemical or physical vapor infiltration). The advantages and disadvantages of these techniques are discussed in details, and the according solutions for solving the problems of each technique are further proposed. The infiltration kinetics of processing carbides are also discussed in details. The investigated properties of wood-derived carbides are summarized, which includes the mechanical properties and thermal properties. The potential applications of wood-derived carbides are explored, along with an overview of the existing challenges and practical limitations. In the end, we provide future perspectives to highlight the future directions of research in this growing area.